The Impact of Comorbidities and Demographic Factors on Ejection Fraction - Cezara Andreea Soysaler; Cătălina Liliana Andrei; Octavian Ceban; Crina Julieta Sinescu (Medicines, 2023)
Heart failure (HF) presents an increasingly significant problem as the population ages. The cause of HF plays a significant role in determining treatment options and outcomes. It is worth noting that several studies have identified gender disparities in both morbidity and mortality, which may suggest differing causes of HF. The purpose of this research is to investigate the influence of various factors, including demographics and comorbidities, on ejection fraction (EF). The objectives of this study involve implementing preventive measures, ensuring timely diagnosis, and implementing interventions that target risk factors and specific comorbidities. These efforts aim to improve the prognosis for individuals affected by heart failure. The main method consists of linear regression. The demographic factors under scrutiny are gender and education, while the comorbidities of interest encompass valvulopathy, ischemia, smoking, obesity, high cholesterol, and diabetes. The main results consist of the fact that high education is associated with a 12.8% better EF on average, while among the factors with a negative role analyzed, ischemia is the most harmful, being 12.8% lower on average. Factors with a smaller impact are smoking, obesity, and high cholesterol. Diabetes does not seem to affect EF.